Teff and Wheat Yield Variation With Phosphorus Application In Jamma District, Ethiopia - Teshome, Habtemariam; Sisay, Kassa; Degu, Adise; Wubu, Tesfaye; Hailu, Tadesse (Journal of Tropical Crop Science, 2023)
Different plant species has different nutrient requirements and utilize nutrients in different ways. Biological activity contributes to P solubilization through mineralization, wheathering, and other physicochemical reactions so that the soil plow layer is the major source of soil availabile P for crops. Ethiopia Ministry of Agriculture and Natural Resource and ATA recommended six types of blended fertilizers (NPSZnB, NPKSB, NPKSZnB, NPSZn, NPSB and NPS) for the Amhara region. Our study was conducted in Jamma districts of eastern Amhara, Ethiopia, during 2018 cropping season to attest the yield of teff (Dega teff) and wheat (Danda’a) due to phosphorus fertilizer application. Fertilizer treatments tested were the recommended dose of N only, recommended dose of NP, 50 kg.ha-1 NPS, 100 kg.ha-1 NPS, and 150kg. ha-1 NPS, set up in a. randomized complete block design with three replication, and conducted on four sites. Our study demonstrated that applications of N and P fertilizers significantly improved grain yield of wheat and teff, and that there was significant yield differences (P < 0.05) between different rates of P fertilizer. Therefore, even though the soil P levels were shown to be sufficient, application of both N and P fertilizer in the Jamma district is essential to increase yield of teff and wheat.